2016
DOI: 10.1038/srep33552
|View full text |Cite
|
Sign up to set email alerts
|

The fungicide triadimefon affects beer flavor and composition by influencing Saccharomyces cerevisiae metabolism

Abstract: Despite the fact that beer is produced on a large scale, the effects of pesticide residues on beer have been rarely investigated. In this study, we used micro-brewing settings to determine the effect of triadimefon on the growth of Saccharomyces cerevisiae and beer flavor. The yeast growth in medium was significantly inhibited (45%) at concentrations higher than 5 mg L−1, reaching 80% and 100% inhibition at 10 mg L−1 and 50 mg L−1, respectively. There were significant differences in sensory quality between bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 45 publications
(51 reference statements)
1
9
0
4
Order By: Relevance
“…Moreover, chemical fungicides cannot be specific for the above pests and they can interfere with the biological function of other microbes, including protechnological organisms involved in food fermentations [15][16][17]. In fact, it has been demonstrated that, in some cases, fungicide residues can lead to modifications in the structure of the cellular membranes and in the metabolism of the yeast, affecting their activity during fermentation [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, chemical fungicides cannot be specific for the above pests and they can interfere with the biological function of other microbes, including protechnological organisms involved in food fermentations [15][16][17]. In fact, it has been demonstrated that, in some cases, fungicide residues can lead to modifications in the structure of the cellular membranes and in the metabolism of the yeast, affecting their activity during fermentation [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It can be explained that S. cerevisiae could form a variety of esters under the action of esterase or alcohol acyltransferase during fermentation ( Saerens et al., 2008 ), and alcohols were also reported as by-products of S. cerevisiae fermentation ( Spinosa et al., 2016 ). Moreover, S. cerevisiae could endow substrates with the characteristic yeast flavor and promote the decomposition of fat and protein to improve flavor ( Kong et al., 2016 ). The alcohols, esters, aliphatic hydrocarbons, and aromatic compounds were more in the fermentation groups than in the CK group.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the addition of cocoa pulp to the fermentation medium and the use of yeast isolated from the spontaneous fermentation of cachaça may have contributed to the increased production of esters, which are among the most important aromatic compounds in alcoholic beverages and are formed in low concentrations during alcoholic fermentation [ 44 46 ]. Of the volatile compounds present in beer, esters are a very important group with regard to the flavor composition.…”
Section: Discussionmentioning
confidence: 99%